PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) MENGGUNAKAN METODE SOSIODRAMA DI KELAS IV SDN 06 SUMANI KECAMATAN X KOTO SINGKARAK - RAHMAWATI, SUSI (Universitas Negeri Padang, 2014)
Abstract Background this research is civic education in elementary school still use teacher center consequently the students are not active in learning. Those problems led to low studens achievement. This research aimed to describe improving the student achievement in civic education by method at grade IV SDN 06 Sumani. Kind of this research is an action research with quantitative and qualitative approach. The result of this research showed that, the student achievement in cycle I was 66,91 and this increased to 77,94 in cycle II. From the result it can be concluded that method increase the student learning achievement in education at grade IV SDN 06 Sumani. Kata Kunci :Hasil belajar, pembelajaran PKN, metode sosiodrama